Efektivitas Model Problem Based Learning Terhadap Metakogitif: Literature Review - Natalia D.M. Silitonga; Jodion Siburian; Lely Mardiyanti (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
This study aims to assess and evaluate the effectiveness of implementing the Problem-Based Learning (PBL) model on metacognition through a literature review of 15 articles published within the last 6 years (2021-2026), consisting of reputable national and international journals. The research method employs a literature review, with the article search process conducted via SINTA, Harzing's Publish or Perish, Google Scholar, and Garuda portals. Journals that were collected and met the predetermined criteria were tabulated, covering the title, author, article type, sample, methods, and research findings. The review results indicate that, in general, Problem-Based Learning is effective in enhancing metacognition. PBL places students at the center of the learning process by confronting them with real-world problems. This approach encourages students' thinking awareness, planning, monitoring, and evaluation of their own thought processes. This study identifies hindering factors such as the requirement for significant time and the influence of students' self-efficacy levels on the success of this model. These findings are expected to provide a comprehensive overview of the strengths and opportunities for PBL implementation in developing metacognitive aspects in the future